guys help me solving this .
Attachments:
![](https://hi-static.z-dn.net/files/dd8/832d33c931cc98f023fa972891e6610a.jpg)
Answers
Answered by
1
Given, cosec (75 + theta) – sec (15 – theta) – tan (55 + theta) + cot (35 – theta)
= cosec(75 + theta) - sec(90-(75+theta) - tan(55+theta)+cot(90-(55+theta)
= cosec(75+theta) - cosec(75+theta) - tan(55 + theta) + cot(55 + theta)
= 0
Hope this helps!
= cosec(75 + theta) - sec(90-(75+theta) - tan(55+theta)+cot(90-(55+theta)
= cosec(75+theta) - cosec(75+theta) - tan(55 + theta) + cot(55 + theta)
= 0
Hope this helps!
Anonymous:
thanka
Answered by
0
He is correct I checked it
Similar questions